Tupistra ashihoi (Asparagaceae), a new species from north-eastern India - Roy, Dilip Kr.; Odyuo, N.; Averyanov, Leonid V. (Phytotaxa, 2017)
Tupistra Ker Gawler (1814: 1655) belonging to Asparagaceae subfamily Nolinoideae (APG 2009, Chase et al. 2009), includes about 26 species (Govaerts 2016). These taxa spread mainly in south and south-east of continental Asia, including Nepal, Bhutan, India, Myanmar, China, Laos, Vietnam, Thailand and Malaysia (Tanaka 2003a, 2003b, 2010a, 2010b, Averyanov et al. 2016). This genus is characterised by leaves with slender petiolar base, relatively large stigma broader than the style, stout columnar style almost as thick as the ovary and usually tuberculate, dirty green, globular berry-like fruit (Tanaka 2003a, 2010a). In India, Tupistra is represented so far by four species, namely Tupistra clarkei Hooker (1894: 325), T. nutans Wall. ex Lindley (1839: 1223), T. stoliczana Kurz (1875: 199) and T. tupistroides (Kunth 1848: 12) Dandy (1932: 329).